The Role of Immunologic Factors In Abortions Observed in Sheep and Goats - Risvanli, Ali; Bulut, Hakan; Zonturlu, Abuzer Gaffar; Demiral, Orkun; Saat, Nevzat; Kilic, Ayse (Veterinary Solutions Llc, 2009)
Abortions and the economic losses they bring about is an important issue in sheep and goat husbandary. Despite many studies conducted on sheep and goats, the underlying reasons behind abortions could not be identified. In the present study, the role of immunologic factors in abortions seen among sheep and goats has been evaluated. The frequencies of anti-sperm antibodies (ASA), anti-zona pellucida antibodies (AZPA), and anti-ovary antibodies (AOA) in the sera of sheep and goats who suffered abortion or had healthy births were determined. The study group consisted of 133 sheep and 101 goats of various breeds and ages that had suffered abortion, and the control group consisted of 101 sheep and 131 goats that had healthy births; 10 ml blood was taken from each subject once. Commercial ELISA test kits determined anti-zona pellucida antibodies in sera. Anti-sperm antibodies and AOS were also detected by the ELISA test, which had been previously developed and modified by various investigators. Eventually, the obtained data were compared between the groups. In conclusion, the frequencies of ASA, AZPA, and AOA in sheep were detected as 0.85%, 0.43%, and 1.23% respectively and the same frequencies in goats were 1.29%, 0.00%, and 0.86%, again respectively. Whereas ASA were 0.75% and AOA were 1.50% in sera of sheep that suffered abortion, ASA and AOA values in sera of goats that suffered abortion were 1.98% and 1.98%, respectively. Anti-zona pellucida antibodies could not be determined in blood sera of animals (both sheep and goats) that suffered abortion. Moreover, in blood sera of both sheep and goats that suffered abortion or had healthy birth, no statistically significant difference regarding the frequency of those 3 antibodies was detected.
Keywords: Abortion; Immunology; Sheep; Goat